1996
DOI: 10.1021/js950375w
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Absorption of Omeprazole from Suppository in Humans

Abstract: The oral absorption of omeprazole is incomplete, in part due to first-pass metabolism. We investigated the feasibility of rectal administration of omeprazole by comparing its absorption from a Witepsol H15-based rectal suppository and an orally administered commercial gelatin capsule in 10 male volunteers. Profiles of plasma concentration between two preparations (20 mg) were not statistically different, indicating that the rate and the extent of absorption were similar. Paired t-test revealed no significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 9 publications
(7 reference statements)
4
21
0
Order By: Relevance
“…, 1996). In humans, no significant differences in the AUC of omeprazole were noted following oral and rectal administration suggesting that the bioavailability is similar between oral and rectal routes (Choi et al. , 1996).…”
Section: Discussionmentioning
confidence: 99%
“…, 1996). In humans, no significant differences in the AUC of omeprazole were noted following oral and rectal administration suggesting that the bioavailability is similar between oral and rectal routes (Choi et al. , 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The 4-h time period used in this study was reported to be an enough time of exposure for examining the effect of the drugs/complexes on gastric and rectal tissues. [25][26][27] The specimens embedded in paraffin using an embedding center and cut into slices. Then, the slices were stained with hematoxylin-eosin and observed under a light microscope (Leitz Laborlux 12 Pols; Ernst Leitz GmbH, Wetzlar, Germany).…”
Section: Histopathological Studymentioning
confidence: 99%
“…[4][5][6] Due to its low bioavailability, short biological half life [7] and hepatic first pass metabolism, various oral formulation of OMZ such as enteric-coated granules [8,9] and tablets [10,11] have been developed with a subsequent 40% increase in oral bioavailability [12] of OMZ but have a wide individual variation of plasma concentration in human. [8][9][10][11] To overcome this problem, alternative dosage forms such as rectal suppository [13] and buccal adhesive tablets [14] were also developed. But all the dosage form of OMZ gives only systemic effect.…”
Section: Introductionmentioning
confidence: 99%